A multiplant transcriptomic atlas reveals conserved and lineage-specific defense architectures in response to Botrytis cinerea - Ritu Singh; Anna Jo Muhich; Cloe Tom; Celine Caseys; Daniel J. Kliebenstein (Proceedings of the National Academy of Sciences, 2026)
Generalist pathogens pose a challenge to plant immunity by infecting diverse hosts while harboring extensive intraspecific genetic variation. Whether evolutionary distant plant lineages rely on a shared immune strategy or deploy distinct, lineage-specific defenses when confronted by these genetically variable members of the same pathogen species remains unresolved. Here, we employed a large-scale cotranscriptomic approach to map the immune landscape of 10 diverse eudicot species infected with 72 genetically distinct Botrytis cinerea isolates. We identified a limited core of evolutionarily conserved defense orthologs, along with a vast landscape of lineage-dependent regulatory genes. Host shared the broad physiological outcome such as metabolic reprogramming, cell wall modification, and suppression of growth-associated processes, yet the regulatory pathways associated with these responses were largely lineage-dependent. Crucially, this immune landscape is dynamically shaped by pathogen diversity. Nearly three-quarters of host transcriptional responses were isolate dependent, with the magnitude of transcriptional reprogramming defined by specific host–isolate combinations rather than a universal species-level response. Even host transcriptional responses correlated with shared virulence factors, including broadly expressed pathogens phytotoxins, were lineage specific. These findings suggest that plant immunity to generalist pathogens is built on conserved physiological outcomes that appear to occur by evolving lineage-dependent regulatory mechanisms. The causal relationship between these lineage-dependent components and the conserved outcomes require further mechanistic investigation. This distinct regulatory architecture creates an immune landscape heavily modulated by specific host–isolate combinations, highlighting the necessity of integrating pathogen diversity into models of plant defense evolution and resistance breeding.